A molecular classification system for estimating radiotherapy response and anticancer immunity for individual breast cancer patients - Zhang, Jiaxuan; Li, Long; Shang, Haotian; Feng, Zhaoyan; Chao, Tengfei (Frontiers in Oncology, 2023)
Objective: Radiotherapy is a cornerstone of breast cancer therapy, but radiotherapy resistance is a major clinical challenge. Herein, we show a molecular classification approach for estimating individual responses to radiotherapy.Methods: Consensus clustering was adopted to classify radiotherapy-sensitive andresistant clusters in TCGA-BRCA cohort based upon prognostic differentially expressed radiotherapy response-related genes (DERRGs). The stability of the classification was proven in the GSE58812 cohort via NTP method and the reliability was further verified by quantitative RT-PCR analyses of DERRGs. A Riskscore system was generated through Least absolute shrinkage and selection operator (LASSO)analysis, and verified in the GSE58812 and GSE17705. Treatment response and anticancer immunity was evaluated via multiple well-established computational approaches.We classified breast cancer patients as radiotherapy-sensitive and -resistant clusters, namely C1 and C2, also verified by quantitative RT-PCR analyses of DERRGs.Two clusters presented heterogeneous clinical traits, with poorer prognosis, older age, more advanced T and more dead status in the C2. The C1 tumors had higher activity of reactive oxygen species and response to X ray, proving better radiotherapeutic response.Stronger anticancer immunity was found in the C1 tumors that had rich immune cell infiltration, similar expression profiling to patients who responded to anti-PD-1, and activated immunogenic cell death and ferroptosis. The Riskscore was proposed for improving patient prognosis. High-Riskscore samples had lower radiotherapeutic response and stronger DNA damage repair as well as poor anticancer immunity, while low-Riskscore samples were more sensitive to docetaxel, doxorubicin and paclitaxel.Our findings propose a novel radiotherapy response classification system based upon molecular profiles for estimating radiosensitivity for individual breast cancer patients, and elucidate a methodological advancement for synergy of radiotherapy with ICB.